ANALYSIS OF SOCIAL, MORAL, AND EDUCATIONAL VALUES IN POLLYANNA NOVEL BY ELEANOR H. PORTER - Natalina Simanjuntak; Rina Octavia Simarmata; Sahat Taruli Siahaan (Jurnal Scientia, 2023)
This study aims to determine (1) the social, moral, and educational values contained in the novel "Pollyanna" by Eleanor H. Porter. (2) the most dominant value of the three values found in the novel "Pollyanna" by Eleanor H. Porter. This study used descriptive qualitative method. The data source is the novel "Pollyanna" by Eleanor H. Porter and the data is in the form of all the sentences in the novel. Data collection techniques in this research used library research, reading techniques, and note-taking techniques. Data analysis carried out in this study was in the form of classifying of data and describing data one by one in the form of paragraphs. The results of this research found that in the novel "Pollyanna" by Eleanor H. Porter there were 36 frequencies of types of social values with percentages (27.5%), 59 frequencies of moral values with presentations (45%), and 33 frequencies of educational values with presentations (27.5%). So of the three values contained in the novel "Pollyanna" by Eleanor H. Porter, the most dominant values in it are moral values with a frequency of 59 and presentation (45%).